Nordic Lights: Work, Management and Welfare in Scandinavia - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2014)
Nordic Lights: Work, Management and Welfare in Scandinavia, edited by Ake Sandberg, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Collective bargaining; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Welfare; Work environment

Où va la protection sociale ? - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2010)
The article reviews the book, "Où va la protection sociale ?," edited by Anne-Marie Guillemard.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Questions sociales : analyses anglo-saxonnes - Socialement incorrect ? - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2011)
The article reviews the book, "Questions sociales : analyses anglo-saxonnes – Socialement incorrect ?," by Julien Damon.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

The Europeanisation of Social Protection - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2009)
The Europeanisation of Social Protection, edited by Jon Kvist and Juho Saari, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; EU membership; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social policy

Le deuxième âge de l'émancipation : la société, les femmes et l'emploi - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2009)
The article reviews the book, "Le deuxième âge de l’émancipation : la société, les femmes et l’emploi," by Dominique Méda an dHélène Périvier.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Ageing Labour Forces - Promises and Prospects - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2008)
Ageing Labour Forces -- Promises and Prospects, edited by Philip Taylor, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Cultural change; International; Labor Unions; Labor force; Older workers; Public policy; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Y-a-t-il une politique européenne d'emploi, de sécurité professionnelle et de dialogue social ? - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2006)
The article reviews the conference papers, "Y-a-t-il une politique européenne d’emploi, de sécurité professionnelle et de dialogue social ?," from the Conférence EUROCAP, Nantes, février 2006.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

East Asian Welfare Regimes in Transition: From Confucianism to Globalisation - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2006)
The article reviews the book, "East Asian Welfare Regimes in Transition: From Confucianism to Globalization," edited by Alan Walker and Chack-kie Wong.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Confucianism; Globalization; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Welfare

Flexible Work Arrangements: Conceptualizations and International Experience - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2005)
The book Flexible Work Arrangements: Conceptualizations and International Experience, by Isik Urla Zeytinoglu, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Flexible hours; International comparisons; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Gender, Discontinued Careers and Low Activity Rates in a Long Life Society - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2004)
While long life society constitutes progress in terms of healthier, better and longer lives, it is also associated with higher pension and health expenditures to an extent that threatens the long term adequacy and sustainability of existing welfare systems. It therefore requires adaptation on the part of society and of social institutions and policies, in particular the labour market and the welfare systems, in order to stem or even reduce the growing dependency ratios of the population. This article thus starts by signalling the six main changes that have occurred in the European Union and US labour markets and the workforce, which concern in particular women in all age groups. It then highlights the main responses of the welfare systems to these changes, emphasizing activation measures and indicating their successes and shortcomings. The article concludes by suggesting policies that may enhance female activity and employment rates, from both the labour supply and demand perspectives.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Gender; International comparisons; LABOR market; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Welfare; Women

Misères du présent, richesse du possible - Sarfati, Hedva (Relations industrielles / Industrial Relations, 1998)
The article reviews the book, "Misères du présent, richesse du possible," by André Gorz.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; work

New Paths in Working Time Policy - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2001)
New Paths in Working Time Policy, edited by jean-Yves Boulin and Reiner Hoffmann, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Human resource management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Working hours

The Political Future of Social Security in Aging Societies - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2007)
The Political Future of Social Security in Aging Societies, by Vincenzo Galasso, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Older people; Reforms; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social security

Faut-il brûler le modèle social français ? - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2007)
The article reviews the book, "Partisanship, Globalization, and Canadian Labour Market Policy: Four Provinces in Comparative Perspective," by Rodney Haddow and Thomas Klassen.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Competing Claims in Work and Family Life - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2008)
Competing Claims in Work and Family Life, edited by Tanja van der Lippe and Pascale Peters, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Labor relations; QUALITY of life; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Work life balance

Le temps de travail de ceux qui ne le comptent pas - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2001)
The article reviews the book, "Le temps de travail de ceux qui ne le comptent pas," by Bernhard Brunhes Consultants, edited by Danielle Kaisergruber.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Kill it to save it – An Autopsy of Capitalism’s Triumph over Democracy - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2017)
This article reviews the book, "Kill it to save it – An Autopsy of Capitalism’s Triumph over Democracy," by Corey Dolgon.